Fuzzy Analytical Hierarchy Process Method for Housing Recommendation Decision Support System - Mala Rosa Aprillya; Yunitarini, Rika; Jauhari, Achmad (Universitas Muhammadiyah Lamongan, 2025)
Population growth in Indonesia that increases every year, encourages people to meet their basic needs, such as housing. Along with this, it encourages developers to offer various types of housing. The problem that is often faced is that consumers often feel confused in finding housing that will be chosen as a residential house that fits the criteria. The purpose of this study is to build a web-based decision support system that can provide housing recommendations that suit buyers by applying the FAHP method. This method is known for its ability to process weighting from several criteria and categories to produce several good alternative choices. There are five criteria that will be used in this study, including price, land area, building area, number of rooms, and number of floors taken from 4 developers in the city of Gresik. The results of the study show that this decision support system can help buyers in providing good housing recommendation solutions. System testing with the black box method shows that this system able to display good information. Based on the results of the questionnaire distributed to buyers, it can be concluded that the existence of this system provides benefits and positive impacts for buyers in choosing housing, with a satisfaction value of 97.2%. Keyword- Decision Support System; Housing; Fuzzy Analytical Hierarchy Process.